Magnetite/Bi‐Doped Carboxylate‐Rich Carbon Spheres – A Highly Efficient Magnetic Photocatalyst Based on Dimetallic FeII/FeIII and BiIII/BiIV Photoredox Cycles. Issue 6 (8th January 2014) - Luo, Zhijun; Qu, Lingling; Han, Tingting; Zhang, Zhen; Shao, Xiaoling; Wu, Xiangyang; Chen, Zhong‐lin
Abstract: A new magnetically separable visible‐light photocatalyst, magnetite/Bi‐doped carboxylate‐rich carbon spheres (Bi‐MCRCSs), was synthesized under ultrasonic irradiation by using magnetite/carboxylate‐rich carbon spheres (MCRCSs) as a precursor. The Bi‐MCRCSs showed much better photocatalytic activity than MCRCSs in the degradation of methylene blue (MB) under visible‐light irradiation ( λ  > 420 nm). Compared with MCRCSs, the Bi‐MCRCSs show more intensive photoabsorption in the whole UV and visible region. In particular, Bi‐MCRCSs display a broad absorption band centered at 550 nm, which give Bi‐MCRCSs advantages over MCRCSs in the utilization of visible light for the degradation of organic pollutants. Owing to the Bi 3+ doping, the Bi III /Bi IV redox cycle can be established in the Fe II /Fe III redox cycle system, which result in the establishment of dimetallic Fe II /Fe III and Bi III /Bi IV photoredox cycles for Bi‐MCRCSs. This dimetallic Fe II /Fe III and Bi III /Bi IV photoredox cycle possesses a significantly enhanced photocatalytic degradation rate compared to that of the monometallic photocycles of Fe II /Fe III for MCRCS. The synergistic effects between the Fe II /Fe III cycle and the Bi III /Bi IV cycle promote the regeneration of Fe II ions in Fe II /Fe III cycle and, hence, accelerate the degradation of organic pollutants. In addition, the magnetic saturation ( M s ) value is about 20 emu/g. After completion of the reaction, the Bi‐MCRCSs could be rapidly separated under an applied magnetic field. Abstract : A dimetallic photocatalytic system based on magnetite/Bi‐doped carboxylate‐rich carbon spheres (Bi‐MCRCSs) shows prominent visible‐light‐photocatalytic properties. The synergistic effects between an Fe II /Fe III cycle and a Bi III /Bi IV photocatalytic cycle promote the regeneration of Fe II ions in the Fe II /Fe III cycle and, hence, accelerate the degradation of organic pollutants.